Wildfires under changing climate, and their environmental and health impacts - Shiv Bolan; Shailja Sharma; Santanu Mukherjee; Daniel F. Gomez Isaza; Essie M. Rodgers; Pingfan Zhou; Deyi Hou; Facundo Scordo; Sudeep Chandra; Kadambot H. M. Siddique; Nanthi Bolan (Journal of Soils and Sediments, 2025)
Purpose Extreme weather events including drought, flooding, and wildfires resulting from climate change can impact ecosystems. Various toxic substances are emitted during wildfires, such as particulate matter and volatile organic compounds, as the frequency and intensity of wildfires rise with climate change. This review aims to focus on the effects of wildfires on environmental health covering contaminants in soil, aquatic and atmospheric environment. Materials and methods A thorough literature search was conducted in Web of Science Core Collections with the following keywords: “wildfire” OR “volatile organic compounds” OR “pollution” OR “contamination” OR “terrestrial pollution” OR “aquatic pollution” OR “atmospheric pollution”. PRISMA flow chart was used to highlight the review's content and provide a more thorough synthesis of relevant studies. Results and discussion Various studies have shown how wildfire emissions affect the public health, although handful information available regarding the environmental health impacts of smoke emissions during wildfires. The post-wildfire trace elemental concentrations and speciation are notably linked to plant species, geology, and topography. Recent studies found increased levels of nitrogen (N), phosphorus (P), dissolved organic carbon (DOC), suspended solids, and water turbidity in lakes within wildfire-burnt watersheds. The response of individual ecosystems to wildfire depends on proximity to the fire, fire characteristics, fuel fee material burned, the effect of fundamental drivers of water quality. Conclusions The findings of this review will encourage and strengthen collaboration between the scientific community and regulatory agencies to better understand how erratic weather events, such as wildfires, may affect the health of people and animals. Graphical Abstract